2018
DOI: 10.2147/opth.s174694
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviridae prevalence in aqueous humor using PCR

Abstract: ObjectiveThe aim of this study was to determine the prevalence of Herpesviridae family in aqueous humor and the prevalence of antibodies against Herpesviridae family in serum.MethodsParticipants undergoing cataract surgery were included in the study. Serum for viral serology including herpes simplex virus (HSV), varicella zoster virus (VZV), Epstein–Barr virus (EBV), and cytomegalovirus (CMV) was collected. Aqueous humor specimen was tapped for PCR analysis.ResultsNinety-two participants were included with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Previous studies showed serological laboratory antibody detection cannot fully reflect intraocular infection. 39 In patients with endogenous infective endophthalmitis, C-reactive protein increased significantly, 40 but for less virulent pathogens, the increase of c-reactive protein was not significant. 41 Although there are still potential confounding factors in the factors related to endophthalmitis, we believe that our data are reliable.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed serological laboratory antibody detection cannot fully reflect intraocular infection. 39 In patients with endogenous infective endophthalmitis, C-reactive protein increased significantly, 40 but for less virulent pathogens, the increase of c-reactive protein was not significant. 41 Although there are still potential confounding factors in the factors related to endophthalmitis, we believe that our data are reliable.…”
Section: Discussionmentioning
confidence: 97%
“…Epstein–Barr virus (EBV) is a member of the Herpesviridae family [ 87 ] and the Lymphocryptovirus genus [ 88 ]. Its genome has the form of linear double-stranded DNA [ 89 , 90 ] and is encased in an enveloped [ 91 ] icosahedral capsid [ 92 ].…”
Section: The Role Of Bcl-xl In Ebv Virus Infectionmentioning
confidence: 99%
“…The aqueous and vitreous PCR confirmed positive for VZV and HHV-6 which were undetected in normal populations. [7]…”
Section: Discussionmentioning
confidence: 99%